2023
DOI: 10.3389/fphys.2023.1052369
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with a previous symptomatic COVID-19 infection have altered heart rate and blood pressure variability during acute exercise

Abstract: Introduction: As the number of COVID-19 cases begin to diminish it is important to turn our attention to any long-term issues that may be associated with a prior infection. Cardiovascular defects have been noted following prior SARS-CoV-2 infections. However, less is known about how a previous infection alters the cardiovascular response to exercise. Further, differences may exist during exercise between previously SARS-CoV-2 positive individuals who had symptoms (symptomatic) relative to those who did not hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In our study, we did not observe a hypertensive response to exercise in any group or new-onset hypertension. However, Chan et al [ 32 ] suggested that a previous symptomatic SARS-CoV-2 infection may alter BP regulation during exercise in healthy individuals due to changes to the autonomic nervous system. In addition, Akpek et al [ 33 ] investigated the effect of COVID-19 on BP, showing significantly higher SBP and DBP at a one-month follow-up compared to admission.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not observe a hypertensive response to exercise in any group or new-onset hypertension. However, Chan et al [ 32 ] suggested that a previous symptomatic SARS-CoV-2 infection may alter BP regulation during exercise in healthy individuals due to changes to the autonomic nervous system. In addition, Akpek et al [ 33 ] investigated the effect of COVID-19 on BP, showing significantly higher SBP and DBP at a one-month follow-up compared to admission.…”
Section: Discussionmentioning
confidence: 99%